In Search of Better Spermatogonial Preservation by Supplementation of Cryopreserved Human Immature Testicular Tissue Xenografts with N-acetylcysteine and Testosterone - Poels, Jonathan; Abou-Ghannam, Gaël; Herman, Sophie; Van Langendonckt, Anne; Wese, François-Xavier; Wyns, Christine (Frontiers in Surgery, 2014)
Controlled slow-freezing is the procedure currently applied for immature testicular tissue cryobanking in clinical practice. Vitrification has been proposed as a promising alternative, with a view to better preserving spermatogonial stem cells for future fertility restoration by autografting in young boys suffering from cancer. It appears that besides the potential influence of the cryopreservation technique used, the transplantation procedure itself has a significant impact on spermatogonial loss observed in ITT xenografts. Eighteen immature testicular tissue pieces issuing from 6 patients aged 2-15 years were used. Fragments of fresh tissue (serving as ungrafted controls), frozen-thawed tissue, frozen-thawed tissue supplemented with N-acetylcysteine and frozen-thawed tissue supplemented with testosterone xenografted to nude mice for 5 days were compared. Upon graft removal, histological and immunohistochemical analyses were performed to evaluate spermatogonia, intratubular proliferation and intrinsic and extrinsic apoptosis. A significant decrease in the integrity of intact seminiferous tubules was found in all three grafted groups. Spermatogonia were observed by immunohistochemistry in all grafted groups, with recovery rates of 67%, 63% and 53% respectively for slow-frozen tissue, slow-frozen tissue supplemented with N-acetylcysteine and slow-frozen tissue supplemented with testosterone. Apoptosis evidenced by active caspase-3 and TUNEL was similar in all grafts. The study is limited by the low availability of immature testicular tissue samples of human origin, and no clear impact of graft supplementation was found. The mouse xenotransplantation model needs to be refined to investigate human spermatogenesis in human immature testicular tissue grafts.